On‐Chip Investigation of Electrocatalytic Oxygen Reduction Reaction of 2D Materials. Issue 47 (17th October 2022) - Qi, Junlei; Wang, Wenbin; Li, Yihan; Sun, Yamei; Wu, Zongxiao; Bao, Kai; Wang, Lingzhi; Ye, Ruquan; Ding, Mengning; He, Qiyuan
Abstract: The on‐chip electrocatalytic microdevice (OCEM) is an emerging platform specialized in the electrochemical investigation of single‐entity nanomaterials, which is ideal for probing the intrinsic catalytic properties, optimizing performance, and exploring exotic mechanisms. However, the current catalytic applications of OCEMs are almost exclusively in electrocatalytic hydrogen/oxygen evolution reactions with minimized influence from the mass transfer. Here, an OCEM platform specially tailored to investigate the electrocatalytic oxygen reduction reaction (ORR) at a microscopic level by introducing electrolyte convection through a microfluidic flow cell is reported. The setup is established on gold microelectrodes and later successfully applied to investigate how Ar‐plasma treatment affects the ORR activities of 2H MoS2 . This study finds that Ar‐plasma treatment significantly enhances the ORR performance of MoS2 nanosheets owing to the introduction of surface defects. This study paves the way for highly efficient microscopic investigation of diffusion‐controlled electrocatalytic reactions. Abstract : An on‐chip electrocatalytic microdevice platform is established for the microscopic investigation of the electrocatalytic oxygen reduction reaction (ORR) of single 2D nanosheets, which is successfully used to demonstrate that Ar‐plasma treatment is effective in enhancing the ORR activity of MoS2 nanosheets at the individual nanosheet level.